Racialized Bodies, Disabling Worlds: Storied Lives of Immigrant Muslim Women by Parin Dossa (Toronto: University of Toronto Press, 2009. 192 pages.) (American Journal of Islam and Society, 2009)
Parin Dossa’s book on the lives of Canadian Muslims provides insightinto the personal stories of women who must grapple with disability in theirdaily lives. It is, therefore, located at the intersection of race, gender, and disabilitystudies and has broad social implications.In her introduction, Dossa discusses the 1967 change in Canadian immigrationpolicies that made immigration easier for a pool of skilled laborersneeded to fill jobs in the economy. Though this search for skilled labor isposited as objective, these policies are biased as regards the relative valueof different bodies. Disabled bodies are valued less in this system. Racialbiases make the situation of racialized disabled people even more difficult.Dossa’s project seeks to investigate the experience of a racialized body ina world that disables. To counter this external lack of value, the women featuredcreate an alternative space of self-value through storytelling ...